Lecithins: A Food Additive Valuable for Antifungal Crop Protection - M. Jolly; R. Vidal; P. A. Marchand (International Journal of Economic Plants)
Lecithins area generic term to designate group of fatty substance in animal and plant tissues. Despite is low solubility in water, lecithin is an excellent emulsifier. It’s used as a food additive for smoothing food textures. Lecithins are also described with plant protection capacity as fungicide. In order to confirm the utility of lecithins in crop protection, experimentations were developed by our institute. Fields trials were coordinated in France by the “HE” Casdar program between 2013 and 2016. The antifungal properties of lecithins were tested against mildews in organic and non-organic farms. Typical used concentrations of lecithins in water are from 75 to 200 g hl-1 and amounts from 75g to 2 kg ha-1 for fungicide uses. Positive results conduct to legalize agricultural application. Lecithins are now approved as basic substance with fungicide properties in EU.